Indexicality of “Kelian” in Student Microteaching Practice: Anthropolinguistic Study - Beslina Afriani Siagian (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
The indexicality study aims to describe the meaning of the variation of the pronoun “kelian” used by students with Batak ethnic background at University of HKBP Nommensen Medan. This study uses a qualitative method with an anthropolinguistic approach. The data of this research is in the form of oral data obtained from the performance of microteaching practices. Data were obtained from 12 recordings, 12 interviews, and participatory observations. The results of this study found that the indexicality of 'kelian' is a communicative expression that can show markers of the speaker's identity, feelings of affection or concern, and community identity. This study concludes that the indexicality of 'kelian' is used as a marker of identity and relations. These findings can be used as a technique to communicate or express knowledge in learning.